Clinical Observation of a Child with Down Syndrome and Glucose and Galactose Malapsorbtion Syndrome - A.I. Kozhemiaka; Ye.P. Zdybskaia; T.V. Sirenko; O.N. Plakhotnaia; N.R. Viun (Zaslavsky O.Yu., 2015)
The article deals with a clinical case of primary glucose and galactose malabsorption syndrome in a child with Down syndrome. Difficulty in diagnosis of glucose and galactose malabsorption syndrome in this observation is due to a combination of this disease with other genetic pathology. The article introduces pediatricians and family doctors to the possible comorbidities of various congenital nosological forms.